THE INFLUENCE OF CULTURAL CHARACTERISTICS ON THE PERCEPTION OF TELEVISION JOURNALISM IN DIFFERENT COUNTRIES: THE IMPORTANCE OF INFORMATION AND LINGUOCULTURAL FACTORS (International journal of artificial intelligence, 2025)
The article analyzes the problem of perception of television journalism in the framework of intercultural communication from a linguocultural perspective. The purpose of the study is to determine the relationship between the perception of television information, the model of trust in it and cultural thinking in different cultures (Uzbekistan, France, Japan and Russia). Based on the theories of intercultural communication and social space of scientists such as Edward Hall, Geert Hofstede and Pierre Bourdieu, the paradigm of high and low context cultures is applied to the process of media perception. The study shows the differences in cultural codes based on the results of a sociological survey conducted by the Uzbek University of Journalism and Mass Communications in 2023, as well as content analysis of the channels France 24, NHK, "Uzbekistan 24" and "Russia 1". The results show that television journalism is not just a system for transmitting information in each country, but also a socio-cultural mechanism that expresses national culture and determines audience trust.